Growth and lipid accumulation in three Chlorella strains from different regions in response to diurnal temperature fluctuations. (February 2016) - Yang, Weinan; Zou, Shanmei; He, Meilin; Fei, Cong; Luo, Wei; Zheng, Shiyan; Chen, Bo; Wang, Changhai
Highlights: Chlorella strains from wide regions were isolated and identified. Three Chlorella strains were closely related by molecular phylogenic analysis. Diurnal temperature fluctuation contributes to lipid accumulation of the strains. Fatty acids compositions were stable under diurnal temperature fluctuation. The strains were suitable for outdoor culture with a wide temperature fluctuation. Abstract: It was economically feasible to screen strains adaptive to wide temperature fluctuation for outdoor cultivation without temperature control. In this research, three Chlorella strains from arctic glacier, desert soil and temperate native lake were isolated and identified. The growth, biochemical composition, lipid content and fatty acid composition of each strain cultured under the mode of diurnal temperature fluctuations were compared. All the three Chlorella strains showed desirable abilities of accumulating lipid under diurnal temperature fluctuations and their fatty acid profiles were suitable for biodiesel production, although the growth and biochemical composition were seemed to be region-specific. The highest lipid content was at 51.83 ± 2.49% DW, 42.80 ± 2.97% DW and 36.13 ± 2.27% DW under different temperature fluctuation of 11 °C, 25 °C, 7 °C, respectively. The results indicated that the three Chlorella strains could be promising biodiesel feedstock for outdoor cultivation by the cultural mode of diurnal temperature fluctuations.